Flexible wood-based thin film based on beveled wood block loaded silver nanowires and preparation method of flexible wood-based thin film

By diagonally cutting wood and combining hot pressing treatment, the problems of uneven penetration of loads and insufficient mechanical properties in traditional wood modification are solved, and uniform penetration of loads and excellent mechanical properties of wood films are achieved.

CN119871624AActive Publication Date: 2025-04-25GUANGXI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510118550.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-25
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

In traditional wood modification, uneven load penetration, limited load capacity and insufficient mechanical properties of wood films.

Method used

By adjusting the cutting angle of the wood, using a bevel cutting method and controlling the cutting angle to 22.5-67.5°, the cavity structure of the wood is optimized, making the load more easily penetrate into the inside of the wood evenly, and the mechanical properties are improved by hot pressing and compacting.

Benefits of technology

It significantly improves the permeability and load capacity of the load, while taking into account the mechanical properties of wood films, solving the contradiction between mechanical properties and load performance in traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119871624A_ABST
    Figure CN119871624A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible wood-based thin film based on beveled wood block loaded silver nanowires and a preparation method of the flexible wood-based thin film, and the preparation method comprises the following steps: 1) cutting wood blocks according to an inclined angle of 22.5-67.5 degrees with the growth direction of wood fibers to obtain wood sheets; (2) lignin in the wood slices is removed through delignification treatment; (3) the wood slices subjected to delignification treatment are soaked with deionized water; (4) loading the silver nanowires on the wood sheet through a vacuum auxiliary method, and drying to obtain the delignification wood sheet loaded with the silver nanowires; and (6) the flexible wood-based thin film based on the beveled wood block loaded with the silver nanowires is obtained through hot pressing treatment. Through oblique cutting of the wood sheet, the permeability of the load in the wood sheet is improved, the load capacity of the wood sheet is improved, and meanwhile, the mechanical property of the wood sheet is considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wood processing, in particular to a method for preparing a flexible wood-based film based on silver nanowires loaded on obliquely cut wood blocks, which can balance the permeability, load capacity and mechanical properties of wood by adjusting the cutting angle of the wood. Background Art

[0002] As a natural and renewable material, wood has a wide range of application potentials in the preparation of functional materials due to its lightweight, high-strength mechanical properties and complex porous cellular structure. In recent years, through the delignification treatment technology, the lignin in wood has been removed to form delignified wood with high porosity and good permeability. Further compression treatment of delignified wood can prepare flexible wood films, which have attracted wide attention in the fields of flexible electronic devices, packaging materials and functional composite materials.

[0003] Flexible wood-based films can be prepared by hot pressing and densification of wood blocks after delignification. However, due to the anisotropy of wood, the cutting direction has a significant effect on the performance of wood-based films. When the wood blocks are cut longitudinally (i.e., the cutting direction is parallel to the growth direction of the wood fibers), the wood-based films after hot pressing and densification show excellent mechanical properties; while when the wood blocks are cut transversely (i.e., the cutting direction is perpendicular to the growth direction of the wood fibers), the mechanical properties of the prepared wood-based films are significantly poor. Therefore, most current studies use the longitudinal cutting method to prepare delignified wood-based films. However, due to the long strip-shaped cell structure of wood, the cell length in the longitudinal cutting direction is long, which makes it difficult for the load to penetrate into the central area of ​​the wood during the penetration process, especially the core part of the wood cell. This uneven load distribution limits the capacity of the load.

[0004] In order to solve the problems of uneven load penetration, limited load capacity and insufficient mechanical properties of wood films in traditional wood modification, it is necessary to develop a flexible wood-based film with excellent load permeability and load capacity, as well as mechanical properties. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a flexible wood-based film based on beveled wood blocks loaded with silver nanowires, which can significantly improve the penetration depth and uniformity of the load while maintaining good flexibility and mechanical properties.

[0006] To achieve the above object, a method for preparing a flexible wood-based film based on an obliquely cut wood block loaded with silver nanowires comprises the following steps:

[0007] 1) Wood pretreatment: Select balsa wood and cut the wood block at an angle of 22.5-67.5° to the growth direction of the wood fiber to obtain wood slices with a thickness of 1-3 mm;

[0008] 2) Delignification treatment: soaking the wood flakes in a sodium chlorite solution at 75-85° C., adjusting the pH of the solution to 4.6, and soaking for 8-10 hours to remove lignin in the wood flakes;

[0009] 3) Cleaning and drying: soaking the wood slices after the delignification treatment in step 2) with deionized water to remove the residual sodium chlorite solution, and freeze-drying the delignified wood slices after the sodium chlorite solution is completely removed to form porous delignified wood slices;

[0010] 4) Modification loading: immersing the porous delignified wood slice in a silver nanowire solution, and using a vacuum-assisted method, allowing the silver nanowires to penetrate into the cell cavity of the wood slice along with the solution;

[0011] 5) Oven drying: drying the delignified flakes loaded with the modified substance in step 4) to obtain delignified wood flakes loaded with silver nanowires;

[0012] 6) Hot pressing treatment: placing the delignified wood slice loaded with silver nanowires in a hot press, clamping the delignified wood slice loaded with silver nanowires with weighing paper and filter paper, and then hot pressing for 6-12 hours to obtain the flexible wood-based film based on the bevel-cut wood block loaded with silver nanowires.

[0013] The present invention adopts the above technical solution, and by adjusting the cutting angle of the wood, using the bevel cutting method and controlling the cutting angle, the cell structure of the wood can be effectively optimized. By cutting the wood block at an angle of 22.5-67.5° oblique to the growth direction of the wood fiber, the exposed area of ​​the wood cell cavity can be effectively increased, while shortening the cell cavity length, which makes it easier for the load to penetrate into the wood evenly. On the other hand, after hot pressing and densification treatment, the mechanical properties of the bevel-cut wood-based film are significantly improved. Although the mechanical properties of the bevel-cut wood-based film are slightly lower than those of the longitudinally cut wood film, they are still better than the cross-cut wood film and have better comprehensive mechanical properties.

[0014] The cutting strategy of the present invention significantly improves the permeability of the load, while effectively increasing the capacity of the wood load, and taking into account the mechanical properties of the wood-based film after hot pressing and densification, providing performance support for further expanding the application of wood-based films in the direction of electromagnetic shielding.

[0015] The flexible wood film prepared by the oblique cutting process of the present invention can show excellent performance in various application fields, such as the preparation of functional composite materials such as electromagnetic shielding, flame retardancy, thermal conductivity and magnetic materials.

[0016] Furthermore, in the step 1), the size of the obliquely cut wood slices is 3 cm×3 cm in length and width, so that the wood slices are more suitable for subsequent steps of impregnation and loading of modifiers.

[0017] Furthermore, in the step 2), the ratio of the mass of the wood slices to the volume of the sodium chlorite solution is 0.5:500-600 g / mL, ensuring that the wood slices can be fully infiltrated in the sodium chlorite solution.

[0018] Furthermore, in the step 2), the solution is adjusted to pH 4.6 by sodium acetate buffer solution.

[0019] Furthermore, in step 3), the temperature of the cold trap for freeze drying is -75°C to -70°C.

[0020] Furthermore, in the step 4) of loading the modifier, vacuum-assisted infiltration of the modifier is performed at a pressure of -0.1 MPa.

[0021] Furthermore, in step 4), the concentration of the silver nanowire solution is 2-10 mg / mL, and the solvent is deionized water or ethanol.

[0022] Furthermore, in step 5), the drying temperature is 60-100°C.

[0023] Furthermore, the temperature of the hot pressing treatment in step 6) is 60-100°C and the pressure is 5-10MPa. The high temperature and high pressure hot pressing treatment promotes the reorganization of cellulose (the main components of the wood flakes after delignification are cellulose and hemicellulose), evaporates water, induces cellulose chemical cross-linking and thermoplastic flow, and at the same time improves the density, smoothness, stability and mechanical properties of the wood-based film by flattening the wood surface.

[0024] The present invention also provides a flexible wood-based film based on the obliquely cut wood blocks loaded with silver nanowires, which is prepared by the above-mentioned preparation method.

[0025] The beneficial effects of the present invention include:

[0026] 1. The present invention adjusts the cutting angle of the wood, that is, cuts the wood block at an angle of 22.5-67.5° oblique to the growth direction of the wood fiber, thereby effectively increasing the exposed area of ​​the wood cell cavity and shortening the cell cavity length, which makes it easier for the load to evenly penetrate into the wood.

[0027] 2. The present invention can effectively increase the capacity of the wood load by cutting the wood block at an oblique angle of 22.5-67.5 degrees while improving the permeability of the load.

[0028] 3. The mechanical properties of the flexible wood-based film based on the beveled wood blocks loaded with silver nanowires are significantly improved after hot pressing treatment, thereby increasing the permeability of the load inside the wood and improving the load capacity of the wood while taking into account the mechanical properties of the wood.

[0029] 4. The flexible wood film prepared by the present invention can be widely used in the preparation of functional composite materials such as electromagnetic shielding, flame retardancy, thermal conductivity and magnetic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1a This is a scanning electron microscope image of the flexible wood-based film prepared in Example 1;

[0031] Figure 1b for Figure 1a A partial enlarged view of

[0032] Figure 2 The stress-strain curves of the flexible wood-based films prepared in Examples 1-3 and Comparative Examples 1-2;

[0033] Figure 3 This is a real shot of the flexible wood-based film prepared in Example 1 in a bent state;

[0034] Figure 4 XRD scans of the flexible wood-based film loaded with silver nanowires prepared in Example 2, the obliquely cut delignified flexible wood-based film not loaded with silver nanowires, and the silver nanowires;

[0035] Figure 5 The electromagnetic shielding effectiveness of the flexible wood-based films prepared in Examples 1-3 and Comparative Examples 1-2 varies with frequency;

[0036] Figure 6 a is a diagram showing that the flexible wood-based film loaded with silver nanowires on the oblique wood block prepared in Example 1 completely wraps the mobile phone to shield the mobile phone signal;

[0037] Figure 6 b is a diagram showing that the flexible wood-based film loaded with silver nanowires on the obliquely cut wood block prepared in Example 1 cannot shield the mobile phone signal when it does not completely wrap the mobile phone. DETAILED DESCRIPTION

[0038] In order to better understand the present invention, the specific method of the present invention is described in detail below in conjunction with the embodiments, but the scope of the present invention is not limited thereto.

[0039] Example 1 Preparation of a flexible wood-based film based on oblique wood blocks loaded with silver nanowires

[0040] 1) Wood pretreatment: Select balsa wood and cut the wood block at an oblique angle of 22.5° to the growth direction of the wood fiber to obtain wood slices with a size of 3 cm×3 cm and a thickness of 2 mm.

[0041] 2) Delignification treatment: at 80° C., the wood slices were immersed in a sodium chlorite solution adjusted to pH 4.6 by a sodium acetate buffer solution, and immersed for 9 hours to remove lignin in the wood slices; since multiple wood slices were immersed at one time in this embodiment, the ratio of the total mass of the wood slices to the volume of the sodium chlorite solution was 0.5:550 g / mL, ensuring that each wood slice was fully delignified.

[0042] 3) Cleaning and drying: soak the delignified wood slices with deionized water for 6 hours, during which the deionized water was replaced 3 times; then dry the wood slices in a freeze-drying device for 48 hours, and the cold trap temperature of the freeze-drying is -75°C to form a porous delignified wood template.

[0043] 4) Modification loading: immersing the porous delignified wood slice in a silver nanowire solution with a concentration of 5 mg / mL (the solvent is deionized water), and at a pressure of -0.1 MPa, using a vacuum-assisted method, allowing the silver nanowires to penetrate into the cell cavity of the wood slice along with the solution;

[0044] 5) Oven drying: drying the delignified wood flakes loaded with the modifier in step (4) at 60° C. for 3 h to obtain delignified wood flakes loaded with the silver nanowire modifier;

[0045] 6) Hot pressing treatment: The delignified wood slice loaded with silver nanowire modification is placed in a hot press, and the delignified wood slice is clamped with weighing paper and filter paper to ensure uniform force, and then hot-pressed at 80°C and a pressure of 5MPa for 10 hours to obtain the flexible wood-based film based on the beveled wood block loaded with silver nanowires.

[0046] Example 2 Preparation of a flexible wood-based film based on oblique wood blocks loaded with silver nanowires

[0047] (1) Wood pretreatment: Select balsa wood and cut the wood blocks at an angle of 45° to the growth direction of the wood fibers to obtain wood slices with a size of 3 cm × 3 cm and a thickness of 2 mm.

[0048] (2) Delignification treatment: The wood slices are immersed in a sodium chlorite solution at 75° C., the solution being adjusted to pH 4.6 by a sodium acetate buffer solution, for 10 hours to remove lignin in the wood. Since multiple wood slices are immersed in this embodiment, the ratio of the total mass of the wood slices to the volume of the sodium chlorite solution is 0.5:600 g / mL, ensuring that each wood slice is fully delignified.

[0049] (3) Cleaning and drying: The delignified wood slices were soaked in deionized water for 6 hours, during which the deionized water was replaced 3 times; then the wood slices were dried in a freeze-drying device for 48 hours, and the cold trap temperature of the freeze-drying device was -70°C to form porous delignified wood slices.

[0050] (4) Modification loading: The porous delignified wood slices were placed in a 10 mg / mL silver nanowire solution (the solvent was deionized water) and the silver nanowires were infiltrated into the cell cavity of the wood slices with the solution by a vacuum-assisted method at a pressure of -0.1 MPa;

[0051] (5) Oven drying: drying the delignified wood flakes loaded with the modifier in step (4) at 80° C. for 2.5 h to obtain delignified wood flakes loaded with the silver nanowire modifier;

[0052] (6) Hot pressing: Place the delignified wood slice loaded with silver nanowire modification in a hot press, and use weighing paper and filter paper to clamp the wood slice to ensure uniform force. Perform hot pressing at 60° C. and 8 MPa for 12 hours to obtain the flexible wood-based film based on the beveled wood block loaded with silver nanowires.

[0053] Example 3 Preparation of a flexible wood-based film based on oblique wood blocks loaded with silver nanowires

[0054] (1) Wood pretreatment: Light wood was selected and the wood blocks were cut at an oblique angle of 67.5° to the growth direction of the wood fibers to obtain wood slices with a size of 3 cm × 3 cm and a thickness of 2 mm.

[0055] (2) Delignification treatment: The wood slices are immersed in a sodium chlorite solution at 85°C. The solution is adjusted to pH 4.6 by a sodium acetate buffer solution and treated for 8 hours to remove lignin in the wood. Since multiple wood slices are immersed in this embodiment, the ratio of the total mass of the wood slices to the volume of the sodium chlorite solution is 0.5:500 g / mL, ensuring that each wood slice is fully delignified.

[0056] (3) Cleaning and drying: The delignified wood slices were soaked in deionized water for 6 hours, during which the deionized water was replaced 3 times; then the wood slices were dried in a freeze-drying device for 48 hours, and the cold trap temperature of the freeze-drying device was -70°C to form porous delignified wood slices.

[0057] (4) Modification loading: The porous delignified wood slices were placed in a 2 mg / mL silver nanowire solution (the solvent was deionized water) and the silver nanowires were infiltrated into the cell cavity of the wood slices with the solution by vacuum-assisted method at a pressure of -0.1 MPa;

[0058] (5) Oven drying: drying the delignified wood flakes loaded with the modifier in step (4) at 100° C. for 2 h to obtain delignified wood flakes loaded with the silver nanowire modifier;

[0059] (6) Hot pressing: Place the delignified wood slice loaded with silver nanowire modification in a hot press, use weighing paper and filter paper to clamp the wood slice to ensure uniform force. Perform hot pressing at 100° C. and 5 MPa for 10 hours to obtain the flexible wood-based film based on the beveled wood block loaded with silver nanowires.

[0060] Comparative Example 1 Preparation of Flexible Wood-Based Films Loaded with Silver Nanowires from Longitudinal Cut Wood Blocks

[0061] (1) Wood pretreatment: Select balsa wood and cut the wood blocks at an angle parallel to the growth direction of the wood fibers to obtain wood slices with a size of 3 cm × 3 cm and a thickness of 2 mm.

[0062] (2) Delignification treatment: The wood slices were immersed in a sodium chlorite solution at 80° C., wherein the solution was adjusted to pH 4.6 by a sodium acetate buffer solution, for 8 hours to remove lignin in the wood.

[0063] (3) Cleaning and drying: The delignified wood slices were soaked in deionized water for 6 hours, during which the deionized water was replaced 3 times; then the wood slices were dried in a freeze-drying device for 48 hours to form porous delignified wood slices.

[0064] (4) Modification loading: The porous delignified wood slices were placed in a 5 mg / mL silver nanowire solution. At a pressure of -0.1 MPa, the silver nanowires were infiltrated into the wood cell cavity along with the solution by a vacuum-assisted method.

[0065] (5) Oven drying: The delignified wood slices impregnated with silver nanowires were placed in an oven and dried at 60 °C for 3 h.

[0066] (6) Hot pressing: Place the delignified wood chips loaded with silver nanowires in a hot press, and use weighing paper and filter paper to clamp the wood chips to ensure uniform force. Perform hot pressing at 80°C and 8MPa for 10 hours to obtain a flexible wood-based film loaded with silver nanowires on longitudinally cut wood blocks.

[0067] Comparative Example 2 Preparation of Flexible Wood-Based Films Loaded with Silver Nanowires from Cross-cut Wood Blocks

[0068] (1) Wood pretreatment: Select balsa wood and cut the wood blocks at a perpendicular angle to the growth direction of the wood fibers to obtain wood slices with a size of 3 cm × 3 cm and a thickness of 2 mm.

[0069] (2) Delignification treatment: The wood slices were immersed in a sodium chlorite solution at 80° C., wherein the solution was adjusted to pH 4.6 by a sodium acetate buffer solution, for 8 hours to remove lignin in the wood.

[0070] (3) Cleaning and drying: The delignified wood slices were soaked in deionized water for 6 hours, during which the deionized water was replaced 3 times; then the wood slices were dried in a freeze-drying device for 48 hours to form porous delignified wood slices.

[0071] (4) Modification loading: The porous delignified wood slices were placed in a 5 mg / mL silver nanowire solution. At a pressure of -0.1 MPa, the silver nanowires were infiltrated into the wood cell cavity along with the solution by a vacuum-assisted method.

[0072] (5) Oven drying: The delignified wood slices impregnated with silver nanowires were placed in an oven and dried at 60 °C for 3 h.

[0073] (6) Hot pressing: The delignified wood pieces loaded with silver nanowires were placed in a hot press, and the wood pieces were clamped with weighing paper and filter paper to ensure uniform force. The hot pressing was performed at a temperature of 80°C and a pressure of 8 MPa for 10 hours to obtain a flexible wood-based film loaded with silver nanowires on a cross-cut wood block.

[0074] The flexible wood-based films prepared in Examples 1-3 and Control Examples 1-2 were subjected to stress-strain curve analysis and electromagnetic shielding performance testing. The stress-strain curve analysis was tested using an electronic universal material testing machine from Instron, USA. Each sample was cut into a dumbbell-shaped specimen (total size, 30×15mm; measurement area, 5×22mm) and tested. The electromagnetic shielding performance was tested using a vector network analyzer using the waveguide method. Each sample was cut into a rectangle (22.9mm×10.2mm), and the electromagnetic parameters (S parameters) of the sample in the frequency range of 8.2-12.4GHz were tested using an Agilent E5071C vector network analyzer. The electromagnetic shielding effectiveness was calculated. The silver nanowire loading was measured by measuring the weight of the wood before and after infiltration to obtain the loading mass of the silver nanowire.

[0075] The tensile strength, electromagnetic shielding performance, and silver nanowire loading of the flexible wood-based films prepared in Examples 1-3 and Comparative Examples 1-2 are shown in Table 1 below.

[0076] Table 1 Performance test of flexible wood-based films prepared in Examples 1-3 and Comparative Examples 1-2

[0077]

[0078] At the same time, the properties of the flexible wood-based films prepared in Examples 1-3 and Comparative Examples 1-2 were characterized.

[0079] (I) Scanning electron microscope

[0080] The flexible wood-based film based on the silver nanowires loaded on the oblique-cut wood block prepared in Example 1 was subjected to electron microscope scanning, and the result is shown in FIG1 . Figure 1a This is a normal electron microscope scan of a flexible wood-based film. Figure 1b for Figure 1a Electron microscope scanning at 6 times magnification. Figure 1a and Figure 1b It can be seen that the cutting direction of the wood film is arranged at a certain angle to the growth direction of the wood. This cutting method can significantly increase the exposed area of ​​the cell cavity and effectively shorten the infiltration path, thereby improving the penetration efficiency of additives inside the wood.

[0081] (II) XRD spectrum analysis

[0082] The XRD patterns of the flexible wood-based film (d-AgNWs@CS) based on the oblique wood block loaded with silver nanowires prepared in Example 2, the oblique delignified flexible wood-based film (d-@CS) without silver nanowires loaded, and the silver nanowires (AgNWs@CS) were analyzed. The results are as follows: Figure 4 As shown. Compared with Example 2, the preparation method of the oblique-cut delignified flexible wood substrate (d-@CS) without silver nanowire loading omitted the modification loading step (4), and the other steps were the same as those in Example 2.

[0083] from Figure 4 It can be seen that the two diffraction peaks at 2θ = 16.1° and 22.6° correspond to the (101) and (002) planes of crystalline cellulose, respectively. In the XRD spectrum of the flexible wood-based film loaded with silver nanowires on d-AgNWs@CS, the typical face-centered cubic (FCC) crystal diffraction peaks of silver can be clearly observed to appear at 38.1° (111), 44.3° (200), 64.4° (220), and 77.5° (311). This result shows that the silver nanowires have been successfully loaded on the flexible wood-based film to form a composite material with uniform structure.

[0084] (III) Stress-strain curve analysis

[0085] The stress-strain curves of the flexible wood-based films based on the oblique wood blocks loaded with silver nanowires prepared in Examples 1-3 and Comparative Examples 1-2 were analyzed. The test results are shown in Tables 1 and Figure 2 shown.

[0086] Combined with Table 1 and Figure 2It can be seen that when the cutting angles are 0°, 22.5°, 45°, 67.5° and 90°, the corresponding fracture strengths of the flexible wood-based film loaded with silver nanowires are 328.8MPa, 200.5MPa, 173.5MPa, 109.8MPa and 20.35MPa, respectively. It shows that with the increase of the cutting angle, the fracture strength of the flexible wood-based film loaded with silver nanowires shows a trend of gradually decreasing. In the process of transitioning from the oblique cutting direction to the transverse cutting direction, that is, when the cutting angle is 90°, the mechanical properties of the flexible wood-based film loaded with silver nanowires decrease significantly. Compared with the flexible wood-based film loaded with silver nanowires in the transverse cutting direction, the flexible wood-based film loaded with silver nanowires in the oblique cutting direction can maintain relatively excellent mechanical properties. Although the mechanical properties of the flexible wood-based film based on the oblique cutting of Examples 1-3 are slightly lower than those of the longitudinally cut wood film, they are still better than the transversely cut wood film and have better comprehensive mechanical properties.

[0087] The flexible wood-based film based on the silver nanowires loaded on the oblique wood block prepared in Example 1 was folded. Figure 3 It can be seen that the flexible wood-based film based on the oblique-cut wood blocks loaded with silver nanowires prepared in Example 1 has good flexibility, which provides a basis for the application of flexible electromagnetic shielding composite materials.

[0088] (IV) Analysis of electromagnetic shielding performance

[0089] The flexible wood-based films based on the silver nanowires loaded on the oblique wood blocks prepared in Examples 1-3 and Comparative Examples 1-2 were tested for electromagnetic shielding effectiveness in the frequency range of 8.2-12.4 GHz. The test results are as follows: Figure 5 shown.

[0090] Combination Figure 5 From the comprehensive analysis of Table 1, it can be seen that compared with the longitudinally cut delignified wood slices, the obliquely cut and cross-cut delignified wood can load more silver nanowires, thereby significantly improving the electromagnetic shielding performance of the flexible wood-based film. In the test range, when the cutting angles are 0° (longitudinal cutting), 22.5°, 45°, 67.5° and 90° (cross-cutting), the electromagnetic shielding effectiveness of the flexible wood-based film loaded with silver nanowires is 18.8-17.1dB, 29.6-27.6dB, 27.4-26.4dB, 31.4-30.2dB and 34.9-30.9dB, respectively. It can be clearly seen that the electromagnetic shielding performance of the cross-cut and obliquely cut flexible wood-based films loaded with silver nanowires is significantly better than that of the longitudinally cut samples. This is mainly because oblique and cross-cut wood are more conducive to the uniform loading and distribution of silver nanowires, which improves the shielding performance of the flexible wood-based film.

[0091] The flexible wood-based film (d-AgNWs@CS) based on the silver nanowires loaded on the oblique wood block prepared in Example 1 is completely wrapped in the mobile phone, which can completely shield the mobile phone signal, making the mobile phone unable to communicate. Figure 6 b. When the mobile phone is not wrapped (part of the mobile phone structure is exposed) and is placed on a flexible wood-based film based on a beveled wood block loaded with silver nanowires, it can communicate normally. Figure 6 It can be seen that the flexible wood-based film based on the silver nanowires loaded on the oblique wood blocks prepared in Example 1 can successfully shield the mobile phone signal and has the electromagnetic shielding function.

[0092] In summary, although the cross-cut wood performs well in terms of silver nanowire loading rate, the mechanical properties of the flexible wood-based film after compression preparation are significantly reduced, showing poor mechanical strength. The longitudinally cut wood performs the opposite. The longitudinally cut wood performs the worst in terms of silver nanowire loading rate, which in turn affects its electromagnetic shielding function, but the longitudinally cut wood film has the best mechanical properties after compression preparation. The oblique-cut flexible wood-based film of the present invention has achieved a good balance between mechanical properties and shielding properties. Taking the breaking strength as an example, compared with the longitudinally cut delignified flexible wood-based film, the mechanical properties of the cross-cut flexible wood-based film are attenuated by 93.81%, and the load-bearing capacity is almost completely lost; while the oblique-cut flexible wood-based film with a cutting angle of 22.5°, its mechanical properties are only attenuated by 39.02%, and it can still maintain a breaking strength of 200.5MPa, while having significantly improved electromagnetic shielding performance (29.6-27.6dB).

[0093] It can be seen that oblique-cut flexible wood-based films provide a new idea for the preparation of wood composite materials. By optimizing the cutting angle, not only can the loading rate of the flexible wood-based film for functional additives (such as silver nanowires) be greatly improved, but the permeability of the film can also be significantly improved. At the same time, it obtains excellent mechanical properties in the subsequent hot pressing treatment, which solves the contradiction between the mechanical properties and functional properties of traditional longitudinal or cross-cut flexible wood-based films, and provides technical support and theoretical basis for the development of high-performance wood-based composite materials.

[0094] The technical solution of the present invention is described, rather than limited. Although the present invention has been described in detail with reference to the aforementioned embodiments, it should be understood by those skilled in the art that the technical solutions described in the aforementioned embodiments can still be modified, or some of the technical features can be replaced by equivalents, and the modifications or replacements made without departing from the spirit of the present invention are all within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a flexible wood-based film based on obliquely cut wood blocks loaded with silver nanowires, characterized in that: The method comprises the following steps: 1) Wood pretreatment: Select balsa wood and cut the wood block at an angle of 22.5-67.5° to the growth direction of the wood fiber to obtain wood slices with a thickness of 1-3 mm; 2) Delignification treatment: soaking the wood flakes in a sodium chlorite solution at 75-85° C., adjusting the pH of the solution to 4.6, and soaking for 8-10 hours to remove lignin in the wood flakes; 3) Cleaning and drying: soaking the wood slices after the delignification treatment in step 2) with deionized water to remove the residual sodium chlorite solution, and freeze-drying the delignified wood slices after the sodium chlorite solution is completely removed to form porous delignified wood slices; 4) Modification loading: immersing the porous delignified wood slice in a silver nanowire solution, and using a vacuum-assisted method, allowing the silver nanowires to penetrate into the cell cavity of the wood slice along with the solution; 5) Oven drying: drying the delignified flakes loaded with the modified substance in step 4) to obtain delignified wood flakes loaded with silver nanowires; 6) Hot pressing treatment: placing the delignified wood slice loaded with silver nanowires in a hot press, clamping the delignified wood slice loaded with silver nanowires with weighing paper and filter paper, and then hot pressing for 6-12 hours to obtain the flexible wood-based film based on the bevel-cut wood block loaded with silver nanowires.

2. The method for preparing a flexible wood-based film based on beveled wood blocks loaded with silver nanowires according to claim 1, characterized in that: In the step 1), the obliquely cut wood slices have a size of 3 cm in length and 3 cm in width.

3. The method for preparing a flexible wood-based film based on beveled wood blocks loaded with silver nanowires according to claim 1 or 2, characterized in that: In the step 2), the ratio of the mass of the wood flakes to the volume of the sodium chlorite solution is 0.5:500-600 g / mL.

4. The method for preparing a flexible wood-based film based on beveled wood blocks loaded with silver nanowires according to claim 1 or 2, characterized in that: In the step 2), the solution is adjusted to pH 4.6 by sodium acetate buffer solution.

5. The method for preparing a flexible wood-based film based on beveled wood blocks loaded with silver nanowires according to claim 1 or 2, characterized in that: In the step 3), the temperature of the cold trap for freeze drying is -75°C to -70°C.

6. The method for preparing a flexible wood-based film based on beveled wood blocks loaded with silver nanowires according to claim 1, characterized in that: In the step 4) of loading the modifier, vacuum-assisted modifier infiltration is performed at a pressure of -0.1 MPa.

7. The method for preparing a flexible wood-based film based on beveled wood blocks loaded with silver nanowires according to claim 1, characterized in that: In the step 4), the concentration of the silver nanowire solution is 2-10 mg / mL, and the solvent is deionized water or ethanol.

8. The method for preparing a flexible wood-based film based on beveled wood blocks loaded with silver nanowires according to claim 1, characterized in that: In the step 5), the drying temperature is 60-100°C.

9. The method for preparing a flexible wood-based film based on beveled wood blocks loaded with silver nanowires according to claim 1, characterized in that: The temperature of the hot pressing treatment in step 6) is 60-100° C. and the pressure is 5-10 MPa.

10. A flexible wood-based film based on oblique wood blocks loaded with silver nanowires, characterized in that: The compound is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Lignin fiber moisture sensor and preparation method thereof

    CN109884136A

  • Transparent wood processing technology for manufacturing high-light-transmittance wooden crafts

    CN113967953A

  • PCB Cleaning Apparatus and PCB Cleaning Method

    KR1020230099599A

  • Flexible wood structures and devices, and methods for fabricating and use thereof

    US20200282591A1

  • Ultra-thin integral composite membrane

    US5547551A